2008
DOI: 10.1093/cvr/cvn001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy is enhanced in PPAR -/- mice in response to chronic pressure overload

Abstract: The present findings show that the absence of PPARalpha results in a more pronounced hypertrophic growth response and cardiac dysfunction that are associated with an enhanced expression of markers of inflammation and extracellular matrix remodelling. These findings indicate that PPARalpha exerts salutary effects during cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
93
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 40 publications
6
93
1
Order By: Relevance
“…In addition, activation of inflammatory signaling pathways has been considered to promote both cardiac hypertrophy and fibrosis, and inhibition of inflammation may attenuate the development of cardiac hypertrophy [34]. In our study, we found that mRNA levels of TNF-α and IL-6 increased in cellular (ET-1) and animal (AAC) models of cardiac hypertrophy, but PMQ treatment could significantly prevent its incremental trend and alleviate progression to cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, activation of inflammatory signaling pathways has been considered to promote both cardiac hypertrophy and fibrosis, and inhibition of inflammation may attenuate the development of cardiac hypertrophy [34]. In our study, we found that mRNA levels of TNF-α and IL-6 increased in cellular (ET-1) and animal (AAC) models of cardiac hypertrophy, but PMQ treatment could significantly prevent its incremental trend and alleviate progression to cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 52%
“…It has been reported that PPAR α, in addition to its well-documented role in cardiac lipid metabolism, modulates immune-inflammatory signaling pathways and the expression of extracellular matrix genes in normal cardiac muscle [36]. Some studies also show that the absence of PPAR α results in a more pronounced hypertrophic growth response and cardiac dysfunction that are associated with an enhanced expression of markers of inflammation and extracellular matrix remodeling [34,37]. These findings indicate that PPAR α exerts salutary effects during cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated that the absence of PPARa results in a more pronounced hypertrophic growth response and signs of functional deterioration (28). A similar relationship between PPARa deficiency and increased oxidative stress was also found in an alcoholic liver disease model (24).…”
Section: Discussionmentioning
confidence: 66%
“…PPAR alpha, the predominant PPAR isoform in the heart, has been implicated in hypertrophic signaling. Smeets et al [14] showed that the absence of PPAR alpha results in a more pronounced hypertrophic growth response and cardiac dysfunction, which are associated with the increased expression of inflammatory markers and extracellular matrix remodeling. PPAR gamma has been shown [15] to attenuate angiotensin-II-induced hypertrophic gene expression and increase cardiomyocyte size in vitro.…”
Section: Discussionmentioning
confidence: 99%